2021
DOI: 10.2196/25014
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Social Media Use to Augment Health Care Among Adolescents and Young Adults With Cystic Fibrosis: Survey Study

Abstract: Background For individuals with cystic fibrosis (CF), adolescence and young adulthood are times of significant vulnerability and have been associated with clinical and psychosocial challenges. Social media may offer innovative care delivery solutions to address these challenges. Objective This study explored motivations and attitudes regarding current social media use and preferences for a social media platform in a sample of adolescents and young adult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The COVID-19 pandemic has forced us to consider the incorporation of alternative models of care delivery. As noted in our study [ 2 ], social media is a model with potential to address compliance, social support, reduce isolation, and other vulnerabilities. The authors raise the question about medical misinformation and the potential adverse implications it may impart in care delivery.…”
mentioning
confidence: 87%
“…The COVID-19 pandemic has forced us to consider the incorporation of alternative models of care delivery. As noted in our study [ 2 ], social media is a model with potential to address compliance, social support, reduce isolation, and other vulnerabilities. The authors raise the question about medical misinformation and the potential adverse implications it may impart in care delivery.…”
mentioning
confidence: 87%
“…Parents often become their children's information sources (Bray & Sinha, 2017). Social media and online sources become the gateway of normalization, social support, comparison, patient empowerment, dissatisfaction with healthcare or HCPs, and referral networks (Perkins et al, 2021; Smailhodzic et al, 2016). Reppucci et al (2022) identified 96 Instagram and 57 Twitter accounts and 94 Facebook pages or groups dedicated to pediatric colorectal information sharing.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Limited research has analyzed AYAs’ use of commercial social media platforms specifically for adherence, such as strategies for remembering and organizing medications. A few studies have investigated AYAs’ use of social media for self-management information more broadly (e.g., looking up information about their specific disease or treatment), generally finding that small subsets of AYAs utilized social media for this purpose (e.g., Anikputa & Horner, 2021; Malloy et al, 2022; Perkins et al, 2021). For example, when Instagram posts from AYAs with inflammatory bowel disease were coded for disease self-management information, only 3% of posts met inclusion criteria, with these posts covering topics such as dietary changes, symptoms and complications, and navigating the health care system (Malloy et al, 2022).…”
Section: Topical Reviewmentioning
confidence: 99%